Copper foam modified electrodes for CO₂ electroreduction: A study on deposition potential effect and flow cell performance - Riyanto, Hanzhola Gusman; Pasaribu, Lewita; Rachman, Fathur; Magdalena, Octaviany; Sanjaya, Afiten Rahmin (Environmental and Materials, 2025)
Background: The development of effective electrochemical conversion technologies is imperative due to the rising global CO2 emissions. A promising platform for CO2 reduction to formate is copper electrode, which can stabilize the carbon dioxide radical that is essential for CO2 conversion. Methods: In this work, Cu foam was electrodeposited in situ on a copper plate with sodium citrate acting as a capping agent (CuF@Cu), with variation of potential deposition were 3V and 5V. Findings: The foam structure of Cu in Cu electrode was confirmed with SEM and XRD measurements for both potential deposition variations. Furthermore, CO2 electroreduction was carried out in a flow cell under ideal conditions, which included aeration for 20 minutes, a flow rate of 75 mL min⁻¹, and an applied potential of −0.33 V vs. Ag/AgCl. For formic acid conversion, the Faradaic efficiency rose from 14.18% (Cu bare) to 26.73% (CuF@Cu 3V) which an 88.7% improvement over bare copper. Conclusion: The enhanced performance is attributed to the increased surface area and three-dimensional foam structure, which augments active sites for CO₂ activation. This work demonstrates that simple electrodeposition of copper foam is an effective strategy for improving electrochemical CO₂ reduction efficiency. Novelty/Originality of this article: These findings demonstrate that CuF@Cu makes using this straightforward electrodeposition technique a viable option for CO2 to formate conversion.